(3cJGH aj GdSjQI hGdaJhMGJs
(3ChdgG (B:s
(3PcQ ESdGe GdfLGTj aj cJGH QShd Gddg Udi Gdg Ydjg hSde eY YeQh Hf CejI GdVejQi s
(3BNQgG (B:s
(3jRhQc Yf TMW GdeRGQ eSdekG ajdbGc HGdENdGU de jJfcH Gdge Udi Ydi SjOfG eMeO hYdi Bdg hGdMeO ddg QH GdYGejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B341 s
(3eUOQ GbJfGA GdCUd (B:s
(3djHjG (B- (3ecJHI GdChbGa , WQGHdS GdZQH (B(22) s
Keywords: (3GdJGQjNs